2005
DOI: 10.1029/2004jd005641
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and mass balance of the Greenland ice sheet: 1958–2003

Abstract: [1] Meteorological models were used to retrieve annual accumulation, runoff, and surface mass balance on a 5 km  5 km grid for the Greenland ice sheet for . We present the first such history that provides insight into seasonal and interannual variability, which should prove useful for those studying the ice sheet. Derived runoff was validated by means of a control model run and independent in situ data. Modeled accumulation has already been validated using shallow ice core data. Surface mass balance (SMB) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
254
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 234 publications
(275 citation statements)
references
References 34 publications
19
254
2
Order By: Relevance
“…To further illustrate the importance of monitoring short scale spatial and temporal variability, we compare our results with accumulation rates derived from an ERA-40 data-based meteorological model (Hanna et al, 2005). The model runs with meteorological data and thus does not depend on density measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further illustrate the importance of monitoring short scale spatial and temporal variability, we compare our results with accumulation rates derived from an ERA-40 data-based meteorological model (Hanna et al, 2005). The model runs with meteorological data and thus does not depend on density measurements.…”
Section: Resultsmentioning
confidence: 99%
“…1). The estimates obtained are compared with snow accumulation rates derived from a weather prediction numerical model run retrospectively using data from the European Centre for Medium-Range Weather Forecast (ECMWF) 45-year (1957-2002) reanalysis ERA-40 and ECMWF operational analysis from 2002 (Hanna et al, 2005(Hanna et al, , 2006(Hanna et al, and 2008. This model has been recently corrected and calibrated for Greenland with recent field measurements .…”
Section: Introductionmentioning
confidence: 99%
“…The PDDM was driven with precipitation and 2 m -air temperature fields. The latter was corrected for biases using empirically-derived lapse rates at a 0.5°by 0.5°resolution [Hanna et al, 2005]. The additional input required to drive the EBSM includes downward shortwave and longwave radiation, surface pressure, wind field and 2 m-atmospheric humidity.…”
Section: Methodsmentioning
confidence: 99%
“…[4] Each model was first tuned to produce annual runoff rates close to estimates by Hanna et al [2005]. To this end, they were forced with 6-hourly European Centre for Medium-range Weather Forecast (ECMWF) reanalysis (ERA-40) data for the period 1991 -2000.…”
Section: Methodsmentioning
confidence: 99%
“…To prescribe boundary conditions for temperature and humidity, we used ERA-40 data (Uppala et al, 2005), since the ECMWF reanalysis data sets have been shown to be quite realistic in representing important climate variables for the Greenland region (Hanna and Valdes, 2001;Hanna et al, 2005). Monthly climatological fields (averaged from 1958 to 2001) of temperature and relative humidity from the 2.5 • ERA-40 grid were bi-linearly interpolated to the Cartesian 100 km grid used in REMBO.…”
mentioning
confidence: 99%